Effect of Ethanolic Extract of Moringa (Moringa oleifera, Lam.) Leaf on Seminiferous Tubules of Wistar Rats (Rattus norvegicus) Model of Metabolic Syndrome - Devitasari, Sade; Pesik, Riza Novierta; Subandono, Jarot; Setyawan, Novan Adi (Smart Medical Journal, 2023)
Introduction: Metabolic syndrome define as symptoms of body abnormalities that increased reactive oxygen species and cause disturbances of the germ cell layer thickness in seminiferous tubules. The content of Moringa oleifera has anti-diabetic, anti-dyslipidemia, and hypotensive effects. This study aimed to find out the effect of ethanolic extract of moringa leaves (Moringa oleifera, Lam.) on the histopathology of seminiferous tubules of Wistar rats (Rattus norvegicus) induced metabolic syndrome with Streptozotocin-Nicotinamide and high-fat diet.Methods: This research was experimental post-only control group design. The subjects were 30 male Rattus norvegicus grouped into normal group (K1), metabolic syndrome group (K2), and 3 metabolic syndrome groups with ethanolic extract of moringa leaf at doses of 150 mg/kg (K3), 250 mg/kg (K4) and 350 mg/kg   of body weight (K5).Results: Thickness of tubules (µm) of group K1 (107.48±10.74), K2 (53.87±25.09), K3 (80.52±3.50), K4 (81.94±9.40), K5 (94.04±8.66). Average number of cell layers of group K1 (8.00±1.09), K2 (3.65±1.35), K3 (5.99±0.36), K4 (6.57±0.36), K5 (6.72±0.20). There was a significant difference in tubule wall thickness and the number of cell layers between the five groups (p<0.05). The K3, K4, and K5 differed significantly from the K2 (p<0.05). K5 has value closest to K1. Conclusion: Ethanolic extract of moringa (Moringa oleifera, Lam.) leaf increased the wall thickness and number of cell layers of seminiferous tubules of Wistar rats (Rattus norvegicus) model of metabolic syndrome with ethanolic extract of moringa leaf at doses of 350 mg/kg of body weight most effectively improved the histopathological of the seminiferous tubules.